Applying the Capabilities Approach to Disability and Education - Riddle, Christopher (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2021)
This paper aims to establish three things. First, that the capabilities approach is the best candidate for an adequate theory of justice to provide just educational opportunities for people with intellectual disabilities. Second, that the capabilities approach, while possessing many merits over rival conceptions of justice, must acknowledge that a prioritization of some capabilities over others is essential. Third and finally, that intellectual disability presents a particularly urgent case for educational justice, because those with intellectual disabilities are historically under-serviced within educational institutions and stand to lose much more than others because of the potential for the compounding of corrosive disadvantage. A stronger claim to justice for people with intellectual disabilities represents a potential for change in the policy and funding associated with education more generally, and for people with intellectual disabilities more specifically.